2021 European guideline on HIV testing in genito‐urinary medicine settings. (5th March 2021) - Gökengin, D.; Wilson‐Davies, E.; Nazlı Zeka, A.; Palfreeman, A.; Begovac, J.; Dedes, N.; Tarashenko, O.; Stevanovic, M.; Patel, R.
Abstract: Testing for HIV is critical for early diagnosis of HIV infection, providing long‐term good health for the individual and prevention of onward transmission if antiretroviral treatment is initiated early. The main purpose of the 2021 European Guideline on HIV Testing in Genito‐Urinary Settings is to provide advice on testing for HIV infection in individuals aged 16 years and older who present to sexually transmitted infection, genito‐urinary or dermato‐venereology clinics across Europe. The guideline presents the details of best practice and offers practical guidance to clinicians and laboratories to identify and offer HIV testing to appropriate patient groups.